Location of a ColE1 deoxyribonucleic acid region that affects the plaque-forming ability of lambda-ColE1 hybrid bacteriophage. - Takeya, T (1979)
The plaque-forming ability of a hybrid phage between plasmidColE1 and phage lambda carrying amber mutations in genes O and P was inhibited by the presence of ColE1 in suppressor-deficient Escherichia coli cells. ColE1 deoxyribonucleic acid regions concerned with this inhibition were examined by using various deletion and transposon insertion derivatives of ColE1, and it was found that the presence of the deoxyribonucleic acid region extending between 420 and 613 base pairs upstream from the initiation site of ColE1 deoxyribonucleic acid replication (J. Tomizawa, H. Ohmori, and R. E. Bird, Proc. Natl. Acad. Sci. U. S. A. 74: 1865--1869, 1977) was essential for this function.